2008
DOI: 10.1182/blood-2007-05-091207
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 signaling modulates HIV-1–induced inflammatory responses and leukocyte transmigration across the blood-brain barrier

Abstract: The relationship among neuroinflammation, blood-brain barrier (BBB) dysfunction, and progressive HIV-1 infection as they affect the onset and development of neuroAIDS is incompletely understood. IntroductionHuman immunodeficiency virus type 1 (HIV-1) infection of the central nervous system (CNS) commonly results in behavioral, motor, and cognitive impairments. [1][2][3] Although disease severity and progression has slowed, in part, as a result of antiretroviral therapy, 76% to 83% of brain autopsies continue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
159
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(167 citation statements)
references
References 68 publications
8
159
0
Order By: Relevance
“…Brain endothelial cell culture and cytotoxicity assays Primary HBMEC were isolated from brain tissue obtained during surgical removal of epileptogenic cerebral cortex in adult patients as described previously 24,25 and provided by Dr Marlys Witte and Dr Michael Bernas (University of Arizona, Tuscon, AZ). These brain tissues were collected under institutional review board-approved protocol at the University of Arizona.…”
Section: Human Monocyte Isolation and Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain endothelial cell culture and cytotoxicity assays Primary HBMEC were isolated from brain tissue obtained during surgical removal of epileptogenic cerebral cortex in adult patients as described previously 24,25 and provided by Dr Marlys Witte and Dr Michael Bernas (University of Arizona, Tuscon, AZ). These brain tissues were collected under institutional review board-approved protocol at the University of Arizona.…”
Section: Human Monocyte Isolation and Cultivationmentioning
confidence: 99%
“…Routine evaluation for von Willebrand factor, Ulex europeus lectin, and CD31 (all from Abcam, Cambridge, MA) demonstrated that cells were .99% pure. Freshly isolated cells were cultured as we previously described, 24,25 and cells at passage 2-4 were used in this study. To determine any potential toxic effects of nanoART on HBMEC, confluent cells were treated with nanoART at 0.1 mM to 0.27 mM for 2 hours at 37°C, 5% CO 2 .…”
Section: Human Monocyte Isolation and Cultivationmentioning
confidence: 99%
“…It has previously been reported that blood-borne IL-6 was able to alter the brain function by crossing the blood-brain barrier (Banks et al, 1994), which supports the idea that IL-6 in CSF, at least to some portion, may be derived from the periphery. Furthermore, it was suggested that circulating IL-6 was able to increase the vascular permeability of blood vessels in the blood-brain barrier (Paul et al, 2003) and to activate signal transducers and activators of transcription (STAT) 1 and 3 (Rummel et al, 2006), which have been described to be implicated in the damage of blood-brain barrier (Chaudhuri et al, 2008). However, with the current experimental approach we were not able to distinguish centrally produced IL-6 from IL-6 in the periphery, an issue that requires further examination.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes, PBMC, and peripheral blood lymphocytes (PBL) were obtained by countercurrent centrifugal elutriation of leukopheresis packs from HIV-1, HIV-2, and hepatitis B-seronegative donors, and monocyte-derived macrophages (MDM) obtained as previously described (23). Cell culture, HIV-1 infection, and experiments assessing the effect of PPAR-g on viral infection were performed as detailed in the online supplement.…”
Section: Methods Cell Isolation and Viral Infectionmentioning
confidence: 99%
“…Protein extraction from cells and lung tissues, Western blot analyses, and microscopy were performed as previously described (23) and as detailed in the online supplement.…”
Section: Rna Isolation and Real-time Polymerase Chain Reactionmentioning
confidence: 99%